Contextualized and Localized Supplementary E-Learning Materials in Science 8 Physics - Agbunag, Maylene Ramirez (Future Science / FSH-PH Publications, 2022)
This study is in response to the current situation in the Philippines that aims to support students' learning needs even from the comfort of their own homes, as well as to improve the teaching and learning process through the use of contextualized and localized supplementary e-learning materials for students. This study aimed to develop, evaluate, and determine the effectiveness of contextualized and localized supplementary e-learning materials for Grade 8 students in Science (Physics) at a public national high school in Antipolo City during the school year 2021-2022. The study utilized both descriptive and experimental research designs. The developed materials were evaluated by twenty science experts and twenty science teachers from the City Schools Division of Antipolo. The participants of the study were thirty Grade 8 students. The data gathering instruments used in this study were the questionnaire checklist, pretest, and posttest. The study showed that the developed contextualized and localized supplementary e-learning materials in science 8 (Physics) helped in the improvement of the teaching and learning process. It is recommended that the materials be used accordingly and constantly modified for improvement.